2019
DOI: 10.1111/1471-0307.12604
|View full text |Cite
|
Sign up to set email alerts
|

Oil/fat blending strategy for improving milk fat globule membrane stability and its effect on fatty acid composition

Abstract: This study examined the effect of blending with cumin essential oil (CEO) on the stabilisation of milk fat globule membrane (MFGM) emulsions, as well as the particle migration rate, fatty acid composition and phospholipid content after pasteurisation. Blending the MFGM with 20% CEO at pH 6.6 (CM4) led to a decrease in the creaming rate. With increasing CEO ratio, the creaming measurements increased to a 30 mm height with 20% CEO at pH 5.5 (CM3) from 25 mm with 10% CEO at pH 5.5 (CM2). The CM4 migration rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The milk was separated to obtain MFGM and skim milk according to the protocol reported in our earlier works (Ali et al . 2019, 2020), with slight modifications under laboratory conditions. Briefly, the samples were centrifuged at 10 000× g and 4 °C for 20 min (H1850R; Cence Company, Beijing, China) to separate the fat molecules.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The milk was separated to obtain MFGM and skim milk according to the protocol reported in our earlier works (Ali et al . 2019, 2020), with slight modifications under laboratory conditions. Briefly, the samples were centrifuged at 10 000× g and 4 °C for 20 min (H1850R; Cence Company, Beijing, China) to separate the fat molecules.…”
Section: Methodsmentioning
confidence: 99%
“…An isolation method described previously by us and others (Ali et al . 2019, 2020; Wang et al . 2019) was used in this study with slight modifications.…”
Section: Methodsmentioning
confidence: 99%
“…I* is inversely proportional to the volume fraction of the particles (Ali et al . 2019). Id,ø=2d3ø(1g)Qs2d3ø(1g)Qs…”
Section: Methodsmentioning
confidence: 99%
“…Atehli et al (2019) studied the effect of freezing on the physicochemical properties and the microstructure of the MFGM. Ali et al (2019) studied the effect of blending with cumin essential oil on MFGM stability, particle migration rate and MFGM contents after pasteurisation. Houlihan et al (1992) reported that MFGM might breakdown during the heat treatment due to the whey protein adsorption to the surface of fat globule.…”
Section: Introductionmentioning
confidence: 99%